Pregabalin treatment in a 30-year-old patient with Bainbridge-Ropers syndrome: a case-report - Geiser, Marie; Good, Jean-Marc; Guinchat, Vincent (Frontiers in Psychiatry, 2024)
Mr. X is a Swiss patient with Bainbridge-Ropers syndrome clinically and genetically diagnosed at the age of 28. He is also known to have severe intellectual disability, autism spectrum disorder and epilepsy since the age of 18. At the age of 30, he was admitted for the first time to a psychiatric crisis unit dedicated to mental disabilities for challenging behavior such as self-aggression (forceful vomiting, scratching himself, pulling out his toe and fingernails or banging his head against the wall), agitation, screaming, dropping to the ground, damaging electronic items, or even displaying hetero-aggressive gestures (trying to bite or pull hair, scratching, kicking, or punching) associated with a drop in mood, withdrawal from usual activities, a drop in social interaction and a tendency to doze off during the day. The introduction of Pregabalin leads to rapid stabilization of the clinical state, almost complete improvement in challenging behavior and gradual withdrawal of other treatments (class 2 analgesics, neuroleptics, antidepressants, and benzodiazepines). At the neurological check-up 9 months after discharge from hospital, clinical stability was confirmed by the surrounding team and the medical observation, with almost complete disappearance of auto-aggressive gestures.